Metformin inhibits glutaminase activity and protects against hepatic encephalopathy. - Javier Ampuero; Isidora Ranchal; David Nuñez; María del Mar Díaz-Herrero; Marta Maraver; José Antonio del Campo; Ángela Rojas; Inés Camacho; Blanca Figueruela; Juan D Bautista; Manuel Romero-Gómez (PLoS ONE, 2012)
AIM: To investigate the influence of metformin use on liver dysfunction and hepatic encephalopathy in a retrospective cohort of diabetic cirrhotic patients. To analyze the impact of metformin on glutaminase activity and ammonia production in vitro. METHODS: Eighty-two cirrhotic patients with type 2 diabetes were included. Forty-one patients were classified as insulin sensitizers experienced (metformin) and 41 as controls (cirrhotic patients with type 2 diabetes mellitus without metformin treatment). Baseline analysis included: insulin, glucose, glucagon, leptin, adiponectin, TNFr2, AST, ALT. HOMA-IR was calculated. Baseline HE risk was calculated according to minimal hepatic encephalopathy, oral glutamine challenge and mutations in glutaminase gene. We performed an experimental study in vitro including an enzymatic activity assay where glutaminase inhibition was measured according to different metformin concentrations. In Caco2 cells, glutaminase activity inhibition was evaluated by ammonia production at 24, 48 and 72 hours after metformina treatment. RESULTS: Hepatic encephalopathy was diagnosed during follow-up in 23.2% (19/82): 4.9% (2/41) in patients receiving metformin and 41.5% (17/41) in patients without metformin treatment (logRank 9.81; p=0.002). In multivariate analysis, metformin use [H.R.11.4 (95% CI: 1.2-108.8); p=0.034], age at diagnosis [H.R.1.12 (95% CI: 1.04-1.2); p=0.002], female sex [H.R.10.4 (95% CI: 1.5-71.6); p=0.017] and HE risk [H.R.21.3 (95% CI: 2.8-163.4); p=0.003] were found independently associated with hepatic encephalopathy. In the enzymatic assay, glutaminase activity inhibition reached 68% with metformin 100 mM. In Caco2 cells, metformin (20 mM) decreased glutaminase activity up to 24% at 72 hours post-treatment (p<0.05). CONCLUSIONS: Metformin was found independently related to overt hepatic encephalopathy in patients with type 2 diabetes mellitus and high risk of hepatic encephalopathy. Metformin inhibits glutaminase activity in vitro. Therefore, metformin use seems to be protective against hepatic encephalopathy in diabetic cirrhotic patients.